Unraveling of cocatalysts photodeposited selectively on facets of BiVO4 to boost solar water splitting - Qi, Yu; Zhang, Jiangwei; Kong, Yuan; Zhao, Yue; Chen, Shanshan; Li, Deng; Liu, Wei; Chen, Yifan; Xie, Tengfeng; Cui, Junyan; Li, Can; Domen, Kazunari; et al. (Nature communications, 2022)
Bismuth vanadate (BiVO 4 ) has been widely investigated as a photocatalyst or photoanode for solar water splitting, but its activity is hindered by inefficient cocatalysts and limited understanding of the underlying mechanism. Here we demonstrate significantly enhanced water oxidation on the particulate BiVO 4 photocatalyst via in situ facet-selective photodeposition of dual-cocatalysts that exist separately as metallic Ir nanoparticles and nanocomposite of FeOOH and CoOOH (denoted as FeCoO x ), as revealed by advanced techniques. The mechanism of water oxidation promoted by the dual-cocatalysts is experimentally and theoretically unraveled, and mainly ascribed to the synergistic effect of the spatially separated dual-cocatalysts (Ir, FeCoO x ) on both interface charge separation and surface catalysis. Combined with the H 2 -evolving photocatalysts, we finally construct a Z-scheme overall water splitting system using [Fe(CN) 6 ] 3−/4− as the redox mediator, whose apparent quantum efficiency at 420 nm and solar-to-hydrogen conversion efficiency are optimized to be 12.3% and 0.6%, respectively. Artificial photosynthesis offers an integrated means to convert light to fuel, but efficiencies are often low. Here, authors report a Z-scheme system utilizing Ir and FeCoO x co-catalysts to enhance charge separation on BiVO 4 facets that achieves high quantum efficiencies for overall water splitting.